Facilitating Crop–Livestock Reintegration in the Northern Great Plains. (1st September 2019) - Kumar, Sandeep; Sieverding, Heidi; Lai, Liming; Thandiwe, Nleya; Wienhold, Brian; Redfearn, Daren; Archer, David; Ussiri, David; Faust, Derek; Landblom, Douglas; Grings, Elaine; Stone, James J.; et al.
Abstract : Integrated crop–livestock systems (ICLSs) can help increase food production while benefiting soils and the environment. This review summarizes recent impacts of ICLSs on crop and livestock production and rural economics and discusses lessons learned in the northern Great Plains (NGP). Research on ICLS conducted in the NGP indicates that the crop residue grazing, swath grazing, and annual forage grazing can positively influence crop production; whereas, livestock performance varies with season, forage nutritive value, and grazing management. Furthermore, ICLSs can reduce the costs and risks of agricultural production. The success of ICLSs in NGP region depends on trade‐offs, planning, economic benefits, policies, regulations, community acceptance, and management skills. The ICLSs could play a strategic role in future agricultural production. The lessons learned from adopting ICLSs in the NGP include the lack of available land for fertilizer (manure) management, that to implement ICLS practices skills and knowledge must be maintained, and ICLS provides an entry point for young farmers and ranchers however capital is needed. These experiences and lessons could be valuable references for producers to adopt ICLSs in the NGP or other regions. Core Ideas Integrated crop–livestock systems positively affect crop production by improving soil health. Common integrated crop–livestock system management techniques can enhance the northern Great Plains crop production. Integrated crop–livestock system livestock performance is impacted by season, forage selection, and management. Integrated crop–livestock systems can increase economic benefits and reduce economic risks. Experiences and lessons in the northern Great Plains could be valuable for other regions to adopt integrated crop–livestock systems.